Kesiapan Tenaga Pendidik Sma Muhammadiyah 1 SurakartaDalam Pembentukan Kompetensi Di Era MasyarakatEkonomi Asean (Mea) - , Purwati; , Prof. Dr. Harsono, SU (2016)
Purwati/A210120099.THE READINESS OF EDUCATORS SMA MUHAMMADIYAH 1 SURAKARTA IN THE ESTABLISHMENT OF THE COMPETENCY IN THE ERA ASEAN ECONOMIC COMMUNITY (AEC). Thesis. Faculty of Education, Universitas Muhammadiyah Surakarta. Juni, 2016. This study aims to investigating the characteristics of the readiness of teachers SMA Muhammadiyah 1 Surakarta in the estalishment of competency in the era of the ASEAN Economic Community (AEC), the particular to determine the characteristics of the readiness of educators SMA Muhammadiyah 1 Surakarta into establishment of competency such as: (1) pedagogical, (2) personal competence, ( 3) social competence, and (4) professional competence. This study is a qualitative research with ethnographic design. Data collection techniques using in-depth interview, observation and documentation. Data validation using by triangulation source and confirmability. The results of this study in SMA Muhammadiyah 1 Surakarta are: (1) Characteristics of the readiness of teachers in the formation of pedagogic competence in the era of the ASEAN Economic Community (AEC) is formed through In House Training (IHT) and the Consultative Subject Teacher (MGMPs) thus forming teachers who have the competence pedagogic in terms of syllabus development, design learning, evaluation of learning outcomes, and the development of teaching methods, (2) Characteristics of the readiness of teachers in the formation of personal competence in the era of the ASEAN Economic Community (AEC) is formed through the study of family Sakinah and coaching principals to form teachers who have personal competence that become teachers of faith and piety and the spirit of the work, (3) Characteristics of readiness of teachers in the formation of social competence in the era of the ASEAN Economic Community (AEC) is formed through the application of the principle of family interaction to form social competencies that a teacher who is not discriminatory, mutual respect, and communication between the various parties, (4) Characteristics of readiness of teachers in the formation of professional competence in the era of the ASEAN Economic Community (AEC) is formed through seminars, workshops, and cooperation with other institutions that make up the professional competence that is able to master the concepts and scientific supporting subjects and develop professionalism on an ongoing basis with a reflective action.